2021
DOI: 10.1111/jvh.13500
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Renal Safety of Tenofovir Alafenamide Fumarate among Chronic Hepatitis B Patients: Real‐World Study

Abstract: Tenofovir alafenamide fumarate (TAF) has high plasma stability resulting in fewer renal adverse events compared to tenofovir disoproxil fumarate (TDF) in chronic hepatitis B (CHB) patients. We aimed to study the effectiveness and renal safety of TAF in a real‐world setting, in patients with or without compromised kidney function. CHB patients (Nucleos(t)ide Analogue [NA]‐naïve or experienced) who received TAF >1 year from 11 academic institutions as part of the Canadian Hepatitis B Network (CanHepB) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
45
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 26 publications
(46 reference statements)
11
45
3
Order By: Relevance
“…ALT normalisation and improvements in bone and renal safety outcomes upon switching to TAF were also reported. Similar results have been reported in other studies, where virological, biochemical and bone and renal safety outcomes were improved or maintained in patients upon switching from TDF to TAF 40‐44,46‐52 …”
Section: Discussion and Clinical Implicationssupporting
confidence: 89%
See 2 more Smart Citations
“…ALT normalisation and improvements in bone and renal safety outcomes upon switching to TAF were also reported. Similar results have been reported in other studies, where virological, biochemical and bone and renal safety outcomes were improved or maintained in patients upon switching from TDF to TAF 40‐44,46‐52 …”
Section: Discussion and Clinical Implicationssupporting
confidence: 89%
“…In Phase 3 studies of CHB patients, TAF demonstrated improved renal and bone safety compared with TDF 19 . Several studies showed that switching from TDF to TAF improved both renal and bone safety 36‐41,43,44,46‐52 . Bone safety was not reported in most studies of TAF switching from ETV or other NAs.…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…TAF increased the ALT normalization rate according to the American Association for the Study of Liver Diseases (AASLD) criteria in the three randomized trials ( Lampertico et al, 2020 ; Agarwal et al, 2018 ). Recently, three retrospective studies in patients with CHB showed similar findings at 12 to 18 months after switching to TAF, but one study showed that the change was not significant at 6 months after switching to TAF ( Toyoda et al, 2021 ; Bernstein et al, 2021 ; Farag et al, 2021 ; Alghamdi et al, 2020 ). Our study showed that the decrease in ALT level persisted after switching to TAF, but the ALT normalization rate was similar at the time of switching and 48 weeks after switching.…”
Section: Discussionmentioning
confidence: 99%
“…TAF is a prodrug of tenofovir (TFV) that has less renal toxicity than TDF. The renal function of patients stabilized at 48 weeks after switching to TAF in a randomized trial and four retrospective studies ( Lampertico et al, 2020 ; Toyoda et al, 2021 ; Bernstein et al, 2021 ; Farag et al, 2021 ; Alghamdi et al, 2020 ). The renal outcome was similar in our study in that the median eGFR decreased during TDF therapy (100.09 vs 91.97 mL/min/1.73 m²) and stabilized at 48 weeks after switching to TAF (93.47 mL/min/1.73 m²).…”
Section: Discussionmentioning
confidence: 99%